Program Layanan Bimbingan Belajar untuk Anak Usia Dini - Hafidz , Nur (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2021)
Tutoring service program for individual assistance in order to overcome problems in children's learning activities so that there are different styles of children's learning in achieving maximum learning performance. Children's tutoring focuses on improving children's learning, children's independent attitudes, children's growth and development, and children's learning achievement. Improving children's learning requires the cooperation of teachers and parents as a source of communication. This program is the first pathway in the Wadas Kelir Play Group non-formal education unit as a child's learning excellence. The organizer of this tutoring service program is the Wadas Kelir Purwokerto Play Group which has programs, orientation services, information services, coaching and distribution, excellence, and learning assistance. The research objective is to find out the aspects of child development through active, educational, and communicative tutoring services programs. So, the achievement of the implementation of tutoring services is having learning resilience in learning habits, such as accustomed to reading or reading books, art school, appreciation of work, and motivation for children's independence. The research method is descriptive qualitative with the subject; classroom teachers, and children involved in learning activities. The research object of the tutoring service program is in the Wadas Kelir South Purwokerto Play Group. The method is by collecting data in the form of documentation, interviews, and observations. As a result, children are confident, skilled in learning, increased language vocabulary, are independent, can read, and have increased reasoning power. From here, the main key to maximum child development is to program children to learn in a fun learning model.